Metabolic syndrome prevalence in Peruvians living below 1 000 and over 3 000 meters - Pajuelo Ramírez, Jaime (2012)
Objectives: To determine and compare the prevalence of metabolic syndrome and its components in Peruvian population living below1000 m and over 3000 m. Design: Data analysis of Encuesta Nacional de Indicadores Nutricionales, Bioquimicos, Socioeconomicosy Culturales Relacionados a las Enfermedades Cronicas Degenerativas 2006. Setting: Instituto Nacional de Salud Centro Nacional deAlimentacion y Nutricion, Ministerio de Salud, Lima, Perú. Participants: Subjects 20 year-old and above. Methods: We included 3384participants aged 20 year-old and above, 2425 living below 1000 m (level-1) and 959 over 3000 m (level-2). Metabolic syndrome wasdefined according to the National Cholesterol Education Program Adult Treatment Panel III (NCEP ATP III) criteria. Main outcomemeasures: Metabolic syndrome and components prevalence. Results: Prevalence of metabolic syndrome was significantly higherin level-1 (19.7%) than in level-2 (10.2%), p<0.001. Prevalence in males was 9.2% in level-1 and 5.1% in level-2, and in females29.9% in level-1 compared to 15.2% in level-2. Central obesity (35.5% vs. 21.1%), elevated blood pressure (20.9% vs. 15.0%),hyperglycemia (3.9% vs. 1.7%), raised triglycerides (31.3% vs. 25.7%), and low concentrations of HDLc (57.4% vs. 52.5%) weresignificantly more prevalent in level-1 compared to level-2 (p<0.05). The most frequent components of metabolic syndrome in menwere hypertriglyceridemia and low HDLc, and in women were low HDLc and central obesity. Conclusions: Metabolic syndrome wassignificantly more prevalent in population under 1000 m; it may be as result of the nutritional, demographic, and socioeconomictransition in this area. Women were more susceptible to cardiovascular risk factors